Replication initiator protein of plasmid R6K autoregulates its own synthesis at the transcriptional step. - Kelley, W (1985)
The replication initiator protein of plasmid R6K preferentially repressed transcription initiated in vitro from the promoter of the initiator protein cistron. DNase I protection experiments revealed that the sequences in the region of the promoter recognized by the initiator protein partially overlapped the sequences of the same promoter recognized by RNA polymerase of Escherichia coli. Competitive DNase I protection experiments revealed that the initiator not only prevented the RNA polymerase from binding to the promoter sequence but also displaced RNA polymerase from preformed enzyme-promoter binary complexes. Thus, the initiator protein acts as a transcriptional repressor of its own cistron by either preventing RNA polymerase from binding to the promoter or by displacing RNA polymerase from promoter-enzyme complexes.